2011
DOI: 10.1117/12.894497
|View full text |Cite
|
Sign up to set email alerts
|

Advancing technology for starlight suppression via an external occulter

Abstract: External occulters provide the starlight suppression needed for detecting and characterizing exoplanets with a much simpler telescope and instrument than is required for the equivalent performing coronagraph. In this paper we describe progress on our Technology Development for Exoplanet Missions project to design, manufacture, and measure a prototype occulter petal. We focus on the key requirement of manufacturing a precision petal while controlling its shape within precise tolerances. The required tolerances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…According to this interpretation, critical structural elements such as the battens which experience strains <0.05% in stowing, deployment or operation [Kasdin 2011] would bend elastically and microcracking would not take place that could affect their performance. Provided they are handled carefully during assembly, microcracking is not an issue for them.…”
Section: Resultsmentioning
confidence: 99%
“…According to this interpretation, critical structural elements such as the battens which experience strains <0.05% in stowing, deployment or operation [Kasdin 2011] would bend elastically and microcracking would not take place that could affect their performance. Provided they are handled carefully during assembly, microcracking is not an issue for them.…”
Section: Resultsmentioning
confidence: 99%
“…Urania: The development of dependable deployment mechanisms have been a major focus of starshade engineering. [39][40][41][42][43] The S5 technology program presented by Willems and Lisman has a number of technology milestones 44,45 that demonstrate the deployment of full-scale subsystems with sufficient accuracy and repeatability, and Arya et al present their solution to this design problem. Figure 7 shows a sequence of such a deployment.…”
Section: Day 2: Starshade Technology and Engineeringmentioning
confidence: 99%
“…In 2012, Kasdin et al 16 demonstrated the manufacturing, assembly, and metrology of a 6-m-long, 2.3-m-wide starshade petal to AE100 μm in-plane accuracy. However, they did not demonstrate petal shape recovery after stowage and deployment.…”
Section: Starshade Mechanical Designmentioning
confidence: 99%
“…The in-plane shape of the petal test article was not controlled to flight-like tolerances since flight-like manufacturing accuracy has been demonstrated in Ref. 16. The objective of this paper is to demonstrate recovery of petal shape after stow-and-deploy cycles, which does not require absolute accuracy.…”
Section: Petal Test Articlementioning
confidence: 99%